Spatiotemporal distribution and risk assessment of organotins in the surface water of the Three Gorges Reservoir Region, China - Gao, Jun-Min; Wu, Lei; Chen, You-Peng; Zhou, Bin; Guo, Jin-Song; Zhang, Ke; Ouyang, Wen-Juan (Chemosphere (Oxford), 2017)
The water quality security of the Three Gorges Reservoir during different operating periods has been a subject of recent concern. This study is the first to report the spatiotemporal variability of organotins (OTs) in surface water under dynamic water level conditions in the Three Gorges Reservoir Region (TGRR). TGRR surface water was collected during three monitoring campaigns to analyze butyltins (BTs) and phenyltins (PTs) using a gas chromatography–mass spectrometry system. Our results showed that TGRR surface water was polluted by BTs and PTs, with mono-OTs being the dominant species. A wide range of BTs and PTs concentrations was observed across the study area, but tributyltin (TBT) displayed extensive spatial distribution, and the highest concentrations consistently occurred in the downstream region of the TGRR study area, with a maximum of 393.35 ng Sn/L in Zigui (S27). The total OTs contamination level decreased over time. The diphenyltin concentration exhibited significant seasonal variation, while other OTs showed seasonal changes only during two monitoring campaigns, with the exception of dibutyltin. An ecological risk assessment indicated that both TBT and triphenyltin posed risks to aquatic organisms in TGRR surface water. We urgently recommend continuous monitoring and further measures to prevent and control OTs pollution in the TGRR. [Display omitted] •The spatiotemporal distribution of OTs in surface water under dynamic water level in the TGRR is reported.•The ƩOTs contamination level decreased with time and showed some seasonal changes in the TGRR.•Hydrological conditions, shipping and agricultural activities affected the spatiotemporal distributions of OTs in the TGRR.•Ecological risk assessment indicated that TBT and TPT pose a risk to aquatic organisms in the surface water of the TGRR.